OPTIMIZATION OF MAKING LIQUID SMOKE FROM COCONUT SHELL AS ORGANIC DISINFECTANT USING TAGUCHI METHOD - Siswanto siswanto; Noto Wiroto; Yan Herdianzah; Samsu Adi Rahman (Center for Study and Journal Management FTI UMI, 2022)
Liquid smoke is effective as a disinfectant Contains anti-bacterial activity. Liquid smoke has the ability to inhibit bacterial growth because it contains phenolic compounds that can bind to bacterial proteins through hydrogen bonds, causing the protein structure to be damaged. Phenol can be found in a variety of consumer products including mouthwash. Phenol is irritating and corrosive to skin and mucous membranes. The shell liquid smoke product containing phenol and acetic acid has an effectiveness comparable to 70% alcohol to be used as a disinfectant at a phenol concentration of 12.5% and is safe to be used as a disinfectant. In the process of making liquid smoke, The quality of liquid smoke is influenced by the pyrolysis temperature, burning time, condensation temperature and dry shell, so that the optimization of the process of making quality coconut shell liquid smoke is made as an organic disinfectant using the Taguchi method, to achieve the specified percentage target so as to produce process standards. The method used is the taguchi . quality control method which combines level factors, namely the pyrolysis temperature factor, burning time, condensation temperature, and shell drying. The optimal results obtained were phenol compounds at rank 1 (A3) process (pyrolysis temperature 1800≤T≤ 2100) , rank 2 (B3) (pyrolysis time 5 hours), rank 3 (D2) (2 days shell drying time) and rank 4 (C1) (condensation temperature 300). And to be used as a disinfectant at a phenol concentration of 12.5% or close to the standard process (A3) (pyrolysis temperature 1800≤T≤ 2100), (B1) (pyrolysis time 1 hour), (C3) (condensation temperature 400) and (D1) (long drying shell 0 days).